The Christmas Café - Evans, Eliza (G. P. Putnam's Sons, 2023)
"Clumsy, earnest baker Sylvie West has worked at the Christmas Café in Silver Bells, Wyoming, ever since her boozy eggnog fruitcake won the town's annual holiday bake-off. Her forever happy place, the café complements her sweet, well-ordered life with her roommates: recently widowed Gramps and her yappy chihuahua-pug, Crumpet. So, when Sylvie learns the café might be sold, she's determined to save it the only way she can: by getting the Holiday Channel crew to set a scene at the café. She's even met the film's charming lead actor, Royce, thanks to Crumpet's meddling. "--